2011
DOI: 10.5051/jpis.2011.41.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Healing pattern of the mucous membrane after tooth extraction in the maxillary sinus

Abstract: PurposeTo investigate the healing pattern of the mucous membrane after tooth extraction necessitated by periodontal disease in the maxillary sinus.MethodsOne hundred and three patients with 119 maxillary sinuses were investigated. Before implant placement, cone-beam computed tomography (CT) scanning was performed. The causes of extraction, the time elapsed since extraction, smoking, periodontal disease in adjacent teeth, and gender were recorded. In addition, the thickness of the mucous membrane of the maxilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 17 publications
(22 reference statements)
6
35
1
2
Order By: Relevance
“…Though this finding is consistent with some previously published studies [27, 28], other studies [21, 31] did report an association. These discrepant findings could be the result of different inclusion criteria in the study design.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Though this finding is consistent with some previously published studies [27, 28], other studies [21, 31] did report an association. These discrepant findings could be the result of different inclusion criteria in the study design.…”
Section: Discussionsupporting
confidence: 93%
“…This finding indicates that clinicians should expect some degree of mucosal thickening when performing sinus augmentation procedures in a previously periodontally involved site. This finding is consistent with several previously published studies [2729]. Phothikhun et al [28] reported that sinuses with severe periodontal bone loss were three times more likely to have mucosal thickening.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, 38 studies were eventually excluded for not meeting the strict inclusion criteria, and 31 studies that reported SMT were considered for qualitative analysis (Table 1). 12,13,15‐18,23‐47 Those studies reporting range or unclear data were excluded for the quantitative analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 19 studies 13,15,17,18,23‐37 fulfilled the inclusion criteria for quantitative assessment. Mean ± SE SMT was 1.17 ± 0.1 mm (95% confidence interval [CI] = 0.89 to 1.44).…”
Section: Resultsmentioning
confidence: 99%
“…Deve-se, portanto determinar corretamente a relação da membrana sinusal com as doenças bucais. (WALLACE, 1996;YOO et al, 2011 A correlação dos diferentes gêneros com a presença de septos, nessa amostra, mostrou uma relação estatisticamente significante para as mulheres, na presença de septos no teto do SM, onde o valor de p foi de 0,042. Não foi encontrado na literatura algum dado que pudesse reforçar esse achado.…”
Section: Resultsunclassified